Perceived Corporate Social Responsibility and Affective Commitment: Evidence from a Multi-Sector PLS-SEM Study of Employee Perceptions in Laghouat, Algeria - Khaled Sief Islam Boukhelkhal; Karim Bouauissa (Journal of Excellence for Economics and Management Research, 2026)
This study examines the effect of employees’ perceived corporate social responsibility (CSR) on affective commitment in Laghouat, Algeria, while testing the mediating roles of organizational identification and job satisfaction. Drawing on Social Identity Theory, Social Exchange Theory, and Stakeholder Theory, CSR is modeled as a higher-order construct covering responsibility toward employees, customers, society/community, and the environment. Data were collected through a structured questionnaire administered to employees from five sectors: oil and gas, manufacturing, public services, agribusiness, and education/health. PLS-SEM using SmartPLS 4 was employed to assess the measurement and structural models, including mediation and sector-based multi-group analysis. Findings show that perceived CSR positively affects affective commitment, both directly and indirectly through organizational identification and job satisfaction. The model explains 51.3% of the variance in affective commitment, with reliability, validity, and predictive relevance meeting accepted thresholds. Sectoral analysis indicates a stronger CSR–commitment relationship in oil and gas and a more indirect expression in public-service-oriented sectors. The study contributes to micro-CSR literature by providing evidence from an understudied Algerian context and identifying organizational identification and job satisfaction as key mechanisms linking CSR perceptions to employees’ emotional attachment to their organization